Terapi Seni Pada Lansia sebagai Upaya Peningkatan Kualitas Hidup di Panti Sosial Rehabilitasi Lanjut Usia Mulia Dharma Kabupaten Kubu Raya - Daevi Khairunisa; Khulul Azmi; Tarisa Miranda; Malisa Malisa (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The elderly often face challenges such as decreased cognitive function, social isolation, depression and anxiety that can affect their overall quality of life. Providing art therapy to the elderly is closely related to understanding its benefits to their physical, mental, and emotional well-being. The purpose of providing art therapy to the elderly is to promote holistic well-being through creative expression, social interaction, and meaningful artistic experiences. The method of implementation is by providing art activities to the elderly who are divided into several groups, carried out for 1 x meeting, each for 1 hour. The target of this activity is the elderly residents of the Mulia Dharma Elderly Rehabilitation Social Institution, Kubu Raya Regency. The results of the activity are in the form of artwork and documentation of art creation activities. Participants showed enthusiasm in participating in art creation activities with flower arranging activities and coloring pictures. Participants showed a happy attitude towards the work produced. Art therapy in the elderly is an effective approach in improving the quality of life in old age. Through creative expression, social interaction, and artistic experiences, older adults can find greater happiness, meaning, and well-being in living life.